2006
DOI: 10.1097/01.gme.0000227329.41458.86
|View full text |Cite
|
Sign up to set email alerts
|

Hot flushes, common symptoms, and social relations among middle-aged nonmenopausal French women in the GAZEL cohort

Abstract: Social relations were associated with psychological and breast symptoms, but not with HFs. The strong association between common symptoms and HFs suggests that biomedical factors have a greater influence than social relations on the occurrence of HFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Indeed, heart discomfort, depressive mood, sleeping problems, and sexual problems were more strongly related to VMS. These associations have been previously reported for postmenopausal 42,43 and premenopausal women, 44 suggesting that these symptoms may have a similar etiopathological origin. The relation between high core body temperature and poor sleeping quality 45 seems to support this fact for both situations: low estradiol and high gonadotropin levels.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Indeed, heart discomfort, depressive mood, sleeping problems, and sexual problems were more strongly related to VMS. These associations have been previously reported for postmenopausal 42,43 and premenopausal women, 44 suggesting that these symptoms may have a similar etiopathological origin. The relation between high core body temperature and poor sleeping quality 45 seems to support this fact for both situations: low estradiol and high gonadotropin levels.…”
Section: Discussionmentioning
confidence: 50%
“…52 The French GAZEL study found that perimenopausal women were more likely to report hot flushes than premenopausal women. 43 Perimenopause-postmenopause status in our series also related to more bothersome VMS; however, this was not as strong as the presence of severe psychological/ urogenital symptoms perhaps because nearly 40% of our premenopausal women also presented VMS. A stronger association between menopause status and VMS has been reported for Australian women.…”
Section: Discussionmentioning
confidence: 52%
“…Alcohol intake is a factor that has been shown in published studies to be associated with both increased 19, 23, 24 and decreased risk 25, 26 of midlife hot flashes. There is some evidence that alcohol consumption increases estrogen concentrations 27, 28 , which would support our finding of a decreased risk of hot flashes with more alcohol intake, as hot flashes are thought to be associated with low estradiol levels.…”
Section: Discussionmentioning
confidence: 99%
“…[4344] In postmenopausal women, access to financial resources is also one of the factors affecting their quality of life. [454647484950] According to some studies, women who had greater access to financial resources and a higher income than other women were suffering lesser physical and psychological-social symptoms. [45] Meanwhile, some researchers argue that satisfaction with financial situation is effective even on sexual satisfaction in postmenopausal women and improves the quality of life, especially in the sexual aspect.…”
Section: Discussionmentioning
confidence: 99%